A practical way to exhibit limitation of strict liability clause in hotels and resorts / Dr. Nuraisyah Chua Abdullah and Ramzyzan Ramly - Abdullah, Nuraisyah Chua; Ramly, Ramzyzan (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2012)
In order to benefit from the limitation of strict liability over lost of guest’s property, exhibition of limitation of liability clause is obligatory under the Innkeepers Act 1952. Majority hotels and resorts exhibit section 4 of the Act on the registration counter or on the wall next to the registration counter. However, such practices are faulty as the exhibition of the legal clause would not be easily understood by the staffs of the establishment as well as the customers. Mere placing only one notice of liability on the registration counter or wall bext to the registration counter is proven ineffective as this would not be visible to the most of the customers. A better design of the limitation of strict liability clause and the method of display and place where the exhibition of the clause should be made is suggested, in order to protect both the hoteliers/resorts and the customers.